2005
DOI: 10.1021/ja056102c
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Pt in Ceria for a Maximum Metal−Support Interaction in Catalysis

Abstract: Conventional supported metal catalysts are metal nanoparticles deposited on high surface area oxide supports with a poorly defined metal-support interface. Typically, the traditionally prepared Pt/ceria catalyzes both methanation (H2/CO to CH4) and water-gas shift (CO/H2O to CO2/H2) reactions. By using simple nanochemistry techniques, we show for the first time that Pt or PtAu metal can be created inside each CeO2 particle with tailored dimensions. The encapsulated metal is shown to interact with the thin CeO2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
145
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(151 citation statements)
references
References 9 publications
6
145
0
Order By: Relevance
“…Interestingly, the side reaction of methanation was inhibited even at 773 K, whereas the side reaction of methanation for the impregnated catalysts reached 11.3% at 773 K. It should be noted that X CO of Pt@Ce 0.67 Zr 0.33 O 2 was a little lower in pure syngas than that of Pt@CeO 2 between 573 K and 773 K, but a little higher in sour syngas. Our results were similar to the results reported by Yeung et al [9]. The X CO of 5% Pt@CeO 2 in our work was 69.8% under the conditions of GHSV = 30000 h − 1 , H 2 O/CO = 4.0 at 673 K, and that was 62.5% for 5% Pt@CeO 2 catalyst in the work of Yeung et al [9] under the conditions of the GHSV = 108000 h smaller than that of Pt@CeO 2 .…”
Section: The Wgs Activity Of the Core-shell Catalyst In Pure And Soursupporting
confidence: 92%
See 2 more Smart Citations
“…Interestingly, the side reaction of methanation was inhibited even at 773 K, whereas the side reaction of methanation for the impregnated catalysts reached 11.3% at 773 K. It should be noted that X CO of Pt@Ce 0.67 Zr 0.33 O 2 was a little lower in pure syngas than that of Pt@CeO 2 between 573 K and 773 K, but a little higher in sour syngas. Our results were similar to the results reported by Yeung et al [9]. The X CO of 5% Pt@CeO 2 in our work was 69.8% under the conditions of GHSV = 30000 h − 1 , H 2 O/CO = 4.0 at 673 K, and that was 62.5% for 5% Pt@CeO 2 catalyst in the work of Yeung et al [9] under the conditions of the GHSV = 108000 h smaller than that of Pt@CeO 2 .…”
Section: The Wgs Activity Of the Core-shell Catalyst In Pure And Soursupporting
confidence: 92%
“…On the other hand, the catalytic active sites were encapsulated in the porous shell structure, which could prevent the sintering of nanoparticles during the reaction process [7,8]. Recently, some core-shell structured catalysts were studied for the WGS reaction [9,10]. Yeung et al [9] reported a novel coreshell Pt ceria catalyst (Pt@CeO 2 ) prepared by microemulsion method for the WGS reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10, 2011 The use of ceria-based catalysts has been well established for a variety of environmental applications, such as oxidation of diesel soot, 10 hydrodesulfurization of fossil diesel oil, 1 low temperature naphthalene and CO oxidation, [11][12][13] H 2 S adsorption, 14 water gas shift process 15 and construction of hydrogen fuel cells. 16 These applications, especially the oxidation processes, are related to oxygen storage capacity (OSC), which reflects the ability of ceria to release oxygen upon reduction of Ce IV and to adsorb oxygen upon the oxidation of Ce III , completing a redox cycle and allowing the in situ regeneration of the catalyst by gas flow. 17 The incorporation of cerium species into zeolites has resulted in materials that combine the high activity of ceria with the high surface area and selectivity of zeolites.…”
Section: Introductionmentioning
confidence: 99%
“…1 Further industrial applications arise from a wide range of favorable properties, particularly resistance to chemical corrosion over a wide temperature range, high melting point, high mechanical strength and good ductility. Platinum is also used in jewelry and dentistry.…”
Section: Introductionmentioning
confidence: 99%